Metode Penilaian untuk Perilaku Profesional: The Professionalism Mini-Evaluation Exercise (P-MEX) Sebuah Alternatif? - Yoga Pamungkas Susani (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2013)
Background: Due to higher attention on professionalism of doctor, greater concern in medical education should be placed on the development of the qualities of professional behavior. Assessment of professional behavior for medical students becomes very essential. However, there is still confusion in selecting and implementing assessment methods. This study aimed to provide an overview of professional behavior assessment and considerations in implementing assessment method especially P-MEX.Method: Relevant literatures are selected as basis of recommendations in P-MEX and professional behavior assessment.Results: P-MEX was discussed using the framework of 7 criteria for good assessment, related to the validity, consistency, equivalence, feasibility, educational effect, catalytic effect and acceptability. Professionalism is multidimensional and one method of assessment cannot give reliable representation of students’ behavior, for that reasons combination of assessment tools is required. The assessment must valid and reliable also. Many methods for assessing professional behavior have been developed, one of them is the Professionalism Mini-Evaluation Exercise (P-MEX), which format is based on Mini-Clinical Encounter Exercise (mini-CEX). This article will describe the outline about professional behavior definition, methods of assessment especially P-MEX, whether P-MEX is a good alternative for assessing professional behavior.Conclusion: P-MEX can be considered as one of assessment method to be applied in assessing student’s professional behavior. However, adapting the instrument to be ready to use here requires a process that can maintain the validity and reliability would be better if the instrument is tailored to Indonesian context.